Pengaruh Dedak Padi Fermentasi pada Silase Isi Rumen Sapi dengan Lama Penyimpanan Berbeda Terhadap Kualitas Fisik, pH dan Kandungan Nutrien Silase - Pramadana, Iyan; Syahrir, Syahrir; Arifuddin, Muh. Sadik (Universitas Tadulako, 2024)
This study, conducted from March to May 2023, aimed to assess the impact of fermented rice bran from cow rumen contents on silage quality, pH, and nutrient content with varying storage times. The experiment took place in Porame Village, Central Sulawesi Province, and Tadulako University's Feed Nutrition Laboratory. The study used molasses, rice bran, EM4, water, and cow rumen waste as materials. Employing a complete randomized design with a 2x3 factorial pattern, the study had 6 treatment combinations and 24 experimental units. Factors included fermented and unfermented rice bran ratios mixed with cow rumen content, and storage times (21, 25, and 30 days). Results from SPSS analysis indicated no significant interaction between fermented rice bran and storage time regarding physical quality and nutrient content. However, the pH of silage was significantly affected. Fermented rice bran (A2) led to a notable pH reduction compared to non-fermented rice bran (A1). In summary, this study concluded that while there's no substantial interaction effect on physical quality and nutrient content, pH measurements are impacted by the use of fermented rice bran.